2016
DOI: 10.1093/molbev/msw001
|View full text |Cite
|
Sign up to set email alerts
|

“Reverse Genomics” Predicts Function of Human Conserved Noncoding Elements

Abstract: Evolutionary changes in cis-regulatory elements are thought to play a key role in morphological and physiological diversity across animals. Many conserved noncoding elements (CNEs) function as cis-regulatory elements, controlling gene expression levels in different biological contexts. However, determining specific associations between CNEs and related phenotypes is a challenging task. Here, we present a computational "reverse genomics" approach that predicts the phenotypic functions of human CNEs. We identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
58
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 53 publications
0
58
0
Order By: Relevance
“…The degree of underestimation of conserved sequence is therefore expected to increase in severity as the evolutionary distance between the reference and focal species increases. Although there is often insufficient power to detect many lineage-specific CEs at recent evolutionary timescales (Ponting, 2008;Rands, Meader, Ponting, & Lunter, 2014), even if the number detected is small, such elements are likely to be of specific interest as putative candidates for lineage-specific function or loss of function (Chan et al, 2010;Lowe, Clarke, Baker, Haussler, & Edwards, 2015;Marcovitz et al, 2016;McLean et al, 2011;Schmidt et al, 2010).…”
mentioning
confidence: 99%
“…The degree of underestimation of conserved sequence is therefore expected to increase in severity as the evolutionary distance between the reference and focal species increases. Although there is often insufficient power to detect many lineage-specific CEs at recent evolutionary timescales (Ponting, 2008;Rands, Meader, Ponting, & Lunter, 2014), even if the number detected is small, such elements are likely to be of specific interest as putative candidates for lineage-specific function or loss of function (Chan et al, 2010;Lowe, Clarke, Baker, Haussler, & Edwards, 2015;Marcovitz et al, 2016;McLean et al, 2011;Schmidt et al, 2010).…”
mentioning
confidence: 99%
“…CNEs have been the subject of intense recent interest. The identification of CNEs has had important implications in enhancing genome annotation (12), investigating signatures of adaptive evolution (13)(14)(15), and identifying putative trait loci (16). CNEs and sequence conservation have also proven crucial in studying the genetic basis of phenotypic diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified a few intriguing examples of gene losses that are 2 associated with phenotypic traits. For example, the enzyme gene GULO is inactivated in independent mammalian lineages that consequently lost the ability to synthesize Vitamin C, and must instead have a constant supply of it in their diet [3,4]; multiple visual system genes are no longer functional in subterranean mammals which live primarily in darkness [5,6]; taste receptor and other genes are lost in fully aquatic cetaceans [7][8][9]; renal transporter genes URAT1, GLUT9 and OAT1 are dead in fruit-eating bats, which could have facilitated their frugivorous diet [10]; the immune genes MX1 and MX2 are eroded in toothed whales, possibly making them more susceptible to certain viral pathogens [11]; and the loss of PON1 in several marine mammals may confer increased vulnerability to agricultural pesticide pollution [12]. Systematic annotation of gene losses across species may therefore not only reveal fascinating evolutionary events and genotype-phenotype relationships, but could also point us to "natural knockout" models for human pathologies that reveal compensating molecular pathways in species missing otherwise-indispensable genes [2,3,13].…”
Section: Introductionmentioning
confidence: 99%